Migrating Vulnerability Marks Homo Sacer Harvest in Bala’s The Boat People - Sharma, Pradip (Dhaulagiri Journal of Contemporary Issues, 2025)
Based on Sri-Lankan civil war and its numerous deaths, Sharon Bala’s novel, Boat People offers this study to examine the vulnerability of the immigrants and anti-refugee politics in Canada. Bala’s narrative of state induced misery that leaves no options to Tamil populations in Sri Lanka to seek refuge abroad offering space to investigate the state racism and human right hypocrisy in the global North. To assay the forcible dislocation of the refugees as a problematic, the study juxtaposes the war-ravaged Sri Lanka and the deceptive West’s deportation, letting this study peruse the state of homelessness of the politically ripped off Tamils homo sacer: the individual stripped of political and legal protections surviving a mere biological life; zoé in a state of exclusion from both law and society. Thus, the article interrogates the statelessness of the Tamils and their narrow escape, aligning with Giorgio Agamben’s homo sacer concept that spotlights the socio-politically abject life akin to Sri Lankan Tamils. While figuring out the existential struggle for dignified human position; biós. Protagonist, Mahindan and others make a herculean attempt for a refuge abroad, making a clarion cal for the humanitarian responsibility. Critiquing the westerner’s double-standard of human rights, the study shows their reduction to persona-non-grata, which scores high in humanities studies.